Evaluation of Drug Planning and Procurement at the Pharmacy Installation of Regional General Hospital Dr. M. Haulussy Ambon (Medico Legal Update, 2020)
Pharmacy Installation is part of the hospital responsible for implementing drug management which includesselection, procurement, distribution and use of the drug. This research aims to evaluate the planning andprocurement of medicines in Dr. M. Haulussy Ambon Hospital Pharmacy Installation. Research usesdescriptive design with retrospective and concurrent data retrieval. Retrospective data is data obtained bytracing the previous year’s documents (secondary data) in 2018 including financial statements, drug planningand use reports, drug procurement reports, and invoices. Retrospective data retrieval is carried out on, thepercentage of conformity between drug planning and the reality of use for each drug. Concurrent data is dataobtained at the time of research or is primary data with in-depth interviews with IFRS officers as well asdiscussions with officers/employees related to drug management. The results showed the Procurement stageof the procurement of funds for each drug item already met the standards. The suitability of planning with thewear reality for each item is not in accordance with the standard (less than 100%). It is expected to cooperatewell with related parties, especially pharmaceutical installations in drug planning and management so thatthe use of existing funds can be more efficient and effective.